Optimizing Child-Friendly School Environments through Ethnopedagogical Management Strategies - Anwar, Herson; Otaya, Lian G; Luneto, Buhari; Ngiode, Syafrin (JURNAL AL-TANZIM, 2023)
This study discusses implementing the Child Friendly School program based on ethnopedagogy concepts in Gorontalo Regency. A descriptive qualitative approach was used through research at MTs Negeri 1 Telaga Biru, SMP Negeri 1 Limboto, and SMA Negeri 1 Telaga. The subjects of the study involved the entire school community directly involved in the program's implementation. Purposive sampling techniques are used to determine research subjects according to the objectives of this study. Data collection instruments consist of interviews, observations, and documentation. The study results show that Ethno pedagogy in the Child-Friendly School Program is integrated into various school activities, such as integrated activities, literacy and environmental management, that refer to Gorontalo's local values and culture. However, there are obstacles and challenges related to school-institution collaboration, school infrastructure renewal, program funding, cultural facilities, geographical location, and foreign cultural influences. This finding is expected to be a reference for other educational institutions in implementing the Child-Friendly School Program and as an evaluation for the three institutions studied to improve and improve the process of implementing this program.